2018
DOI: 10.17576/jsm-2018-4708-25
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Kenaf Yarn Properties as Affected by Different Linear Densities for Woven Fabric Laminated Composite Production

Abstract: Currently, there is a growing interest of using woven material in composite production for many applications such as structural applications, non-structural applications, household utilities, parts for automobile, aerospace components, flooring and ballistic laminate composites. The structure and properties of the woven fabric is very important as it dictate the woven composite properties. The properties of yarn like linear density, twist factor and strength can influence most of the woven fabric properties. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Nevertheless, various factors such as fibre type, yarn sizing, fabric count, or weave structure can influence the strength of the fabric. Numerous researchers have shown that the strength of the fabric depends not just on the yarn’s strength, but also the yarn and fabric structures [ 103 , 107 , 128 ].…”
Section: Factors Influencing Woven Polymer Composites Propertiesmentioning
confidence: 99%
“…Nevertheless, various factors such as fibre type, yarn sizing, fabric count, or weave structure can influence the strength of the fabric. Numerous researchers have shown that the strength of the fabric depends not just on the yarn’s strength, but also the yarn and fabric structures [ 103 , 107 , 128 ].…”
Section: Factors Influencing Woven Polymer Composites Propertiesmentioning
confidence: 99%
“…The sisal yarn is made of a bundle of z-twisted fibers with a twist level about 80 tpm, Figure 8. Mostly, the yarns are z-twisted because the spinning machines are made for right-handed manipulators [69]. The average value of the sisal yarns' diameter is 2.01 ± 0.9 mm ( Table 7).…”
Section: Diameter and Linear Density Of Sisal Yarnsmentioning
confidence: 99%
“…Condition Cellulose Hemicellulose Lignin S. Jose [21] Raw 80.00 -81.00 % 16.00 -19.00 % 4.60 -12.00 % Z. Daud [22] Raw 66.20 % 19.50 % 4.20 % M. Mahardika [18] Raw 62.50 % 13.90 % 15.9 % S. Mishra [20] Raw 70.00 -82.00 % -5.00 -12.00 % Z. Daud [23] Raw 66.20 % 19.50 % 4.28 % M. Mahardika [18] Treated 81.30 % 2.90 % 1.50 % I. Fareez [19] Treated 85.53 ± 2.30 % 0.30 ± 0.90 % 0.40 ± 0.30 % With the above concern, this study's objective is to determine the single fibre tensile properties of the PALF. The output of the research may help to understand the characteristic of the PALF for further application.…”
Section: Authormentioning
confidence: 99%